Infrastruktur dan Kemiskinan di Provinsi Daerah Istimewa Yogyakarta - Sodik Dwi Purnomo; Minadi Wijaya; Heri Setiawan (Majalah Imiah Manajemen & Bisnis, 2021)
The average poverty rate in the Special Province of Yogyakarta is the highest compared to other provinces in Java in 2012 to 2018. The study aims to analyze the impact of economic infrastructure, educational infrastructure and health infrastructure on poverty in the Special Region of Yogyakarta Province. Data analysis using multiple linear regression with panel data equations and data processing using the eviews application. The results showed that economic infrastructure had a significant negative effect on poverty in the Special Region of Yogyakarta Province in 2003 - 2018. Meanwhile, health infrastructure and education infrastructure had no effect on poverty in the Special Region of Yogyakarta Province in 2003 - 2018. The implication of this research is that infrastructure development must be equitable and fair in all districts and cities in the Special Region of Yogyakarta, especially in areas with high poverty rates